Research and Reconciliation - Patten, Herb; Ryan, Robin (The Australian Journal of Indigenous Education, 2001)
This paper is based on a workshop, with the authors co-presented on the politics and practice of research at Trajectories:an International Colloquium on Intercultural Musics in the East Asia/Western Pacific Region, held in the Department of Contemporary Music Studies, Macquarie University, Sydney on March 12, 2001.